Studies on temporal-spatial expression characters of Bt protein in two transgenic hybrid cotton - YU En; CAI Yunfei; ZHAO Rubing; CHEN Jinhong; ZHU Shuijin (浙江大学学报. 农业与生命科学版)
Cotton bollworm, Helicoberpa armigera, was one of the most harmful pests in cotton-production areas all over the world. The transgenic insect resistant cotton with Bt gene from Bacillus thuringiensis was developed to control this pest in 1987. It was increased quickly in recent years, accounting for more than 93% of all cotton planted in China, and huge economic, social, and ecological benefits were obtained.The levels of Bt protein in cotton organs can directly affect the insect resistance of cotton plants. Many reports showed that the Bt cotton expressed the Bt protein at a high level in early season which provided good control of the second generation of cotton bollworm, but it was decreased in middle and late stages which lead to the decrease of the controlling efficacy to bollworm. However, few reports had been found about the levels of Bt protein in different organs and tissues during the whole growth stages of the transgenic hybrid cotton. Whole season levels of Bt protein in two transgenic hybrid cotton, Zheda 13-1 and Zheda 13-2, and their pure line parent, Zayou 2012, were investigated in 2014 in Hangzhou City, Zhejiang Province, located in southeast coastal region of China. Enzyme linked immuno-sorbent assay (ELISA) method was used to quantify Bt protein.The results showed that the Bt protein could be detected in all organs and tissues in the two hybrid cultivars and their parent, however, its levels changed significantly among the different organs from time to time. During the seedling stage, cotyledon was the highest organ, following by the first true leaf. The Bt protein level in root and stem was increased at the beginning, reached the peak value on 33 and 40 days after sowing, respectively for two cultivars, then decreased steadily afterward. In general, the Bt protein in root was much higher than that in stem. In the leaves of the two hybrid cottons, the upper third leaf, Bt protein was high in the early stage, declined in midseason but rebounded in late-season. While for their parent, it was high in early season, then declined steadily in middle and latter season. The difference might relate to the growth habit of the hybrid cotton which kept growing in late-season for relatively long time. So it is suggested that the pesticide control might be necessary for the hybrid cotton in the mid-season of cotton growth. In addition, the study showed that Bt protein contents in the anther and stamens were much higher than those in leaves, squares, bolls, ovules, and petals. While for their parent, it was much lower in the anther and stamens than that in other organs and tissues. It should be studied further whether or not this phenomenon was resulted from the heterosis of the hybrid cotton, the high concentration of Bt protein in the anther and stamens was beneficial to the cotton bollworm control of the hybrid cotton as the cotton bollworms were more interested in the cotton reproductive organs.